2013
DOI: 10.1002/ajmg.a.36322
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic microdeletion of 17p11.2–p12 and duplication of 17q22–q24 in a girl with Smith–Magenis phenotype and peripheral neuropathy

Abstract: We report on a girl with a de novo mosaic derivative chromosome 17 involving a 7.4 Mb deletion of chromosome region 17p11.2 to 17p12 and a duplication of a 12.35 Mb region at 17q22 to 17q24. She was ascertained because of developmental delay, peripheral neuropathy, brachydactyly and minor anomalies. The derivative chromosome was present in approximately 12% of lymphocytes based on FISH studies, and was detected by array comparative genomic hybridization. To our knowledge, this is the third case of mosaicism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The mutations in RAI1 , located in the 17p11.2 locus are known to be responsible for the inversion of the melatonin cycle 24 . However, not all SMS patients with RAI1 mutations or deletions experience sleep disturbances 25 , hence the SMS phenotype may be achieved by complex rearrangements of chromosome 17 that also involve its long arm 26,27 . The observation of DNA methylation changes in the group of genes related to SMS requires further investigation, possibly in occupational cohorts of shift workers, since shift work can lead to circadian misalignments and sleep loss 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The mutations in RAI1 , located in the 17p11.2 locus are known to be responsible for the inversion of the melatonin cycle 24 . However, not all SMS patients with RAI1 mutations or deletions experience sleep disturbances 25 , hence the SMS phenotype may be achieved by complex rearrangements of chromosome 17 that also involve its long arm 26,27 . The observation of DNA methylation changes in the group of genes related to SMS requires further investigation, possibly in occupational cohorts of shift workers, since shift work can lead to circadian misalignments and sleep loss 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Her nerve conduction studies did not show any evidence of peripheral neuropathy. In contrast to BAB485, one mosaic case for the PMP22-RAI1 deletion reported by Goh et al (Goh et al 2014) did have facial features and developmental delays consistent with SMS, as well as hyporeflexia. NCS studies at the age of 7.5 years confirmed polyneuropathy.…”
Section: Resultsmentioning
confidence: 61%
“…Interestingly, there have been reports of rare large deletions that encompass both HNPP and SMS loci and include both PMP22 and RAI1 (Goh et al 2014; Juyal et al 1996; Liu et al 2011; Stankiewicz et al 2003; Trask et al 1996; Zori et al 1993). These deletions have breakpoints that are potentially beyond the regions defined by the LCR-mediated NAHR; thus, a different mechanism may be considered and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The haploinsufficiency of multiple contiguous genes usually results in neurodevelopmental disorders and variable degree of malformations. Differently from larger chromosomal imbalances and aneuploidies, mosaicism has been infrequently reported in microdeletion syndromes (Al‐Zahrani et al, 2011; Anderlid et al, 2014; Goh et al, 2014; Halder et al, 2018; Huynh et al, 2017; Messiaen et al, 2011; Shimada et al, 2014; Taylor et al, 2014; Tekin et al, 2000). Among the few mosaic microdeletion cases described, 22q11.2 microdeletion (Halder et al, 2018) and NF1 atypical microdeletion syndrome (Messiaen et al, 2011) are the most frequently reported.…”
Section: Discussionmentioning
confidence: 99%